PRE-QUESTIONING TECHNIQUE IN IMPROVING STUDENTS’ACHIEVEMENT IN READING NARRATIVE TEXT - Fitriyani, Sari; Marbun, Rismaya; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research focused on the use of pre-questioning in improving students? reading achievement in narrative text. The objective of the research is to find out whether Pre-questioning technique can improve student achievement in reading narrative text of eleventh grade students of SMA 2 Sungai Kakap, Kubu Raya in academic years 2014/2015. The researcher conducted a pre-experimental study with measurement as the technique of collecting data and written test as tool of collecting data. The sample of this study was 32 students. The research finding show that the mean score of pre-test is 42.03; which is categorized as ?Poor?. Furthermore, the mean score of post-test was 67.81; which is categorized as ?Average to Good?. Based on the data analysis, it was found that the effect size of this research is 1.99; which is categorized as ?High Effect?. It can be concluded that the use of pre-questioning technique in teaching reading narrative comprehension can improve the students? reading achievement in narrative text significantly. Keyword: Pre-questioning, Reading Comprehension, Narrative text. Abstrak: Penelitian ini fokus pada penggunaan teknik pre-questioning dalam meningkatkan pemahaman siswa dalam membaca teks narratif. Tujuan melakukan penelitian ini adalah untuk mengetahui apakah pre-questioning teknik dapat meningkatkan pemahaman siswa dalam teks narrative pada siswa kelas sebelas SMA negeri 2 sungai kakap, Kubu Raya pada tahun ajaran 2014/2015. Penelitian dilakukan dalam bentuk penelitian pre-experimental menggunakan tehnik pengukuran sebagai tehnik pengolahan data serta tes tertulis sebagai cara mengumpulkan data. Penelitian ini melibatkan sampel sebanyak 32 siswa. Hasil dari penelitian ini mendapatkan nilai rata rata pre-test nya adalah 42.03; termasuk kategori ?rendah?. Kemudian, nilai rata-rata dari post-test adalah 67.81; termasuk kategori ?rata-rata ke baik?. Berdasarkan analisis data, ditemukan bahwa ukuran efektifitas dari penelitian ini adalah 1.99 termasuk katagori ?efek tinggi?. ini dapat disimpulkan bahwa penggunaan teknik pre-questioning dalam mengajar pemahaman membaca teks narratif dapat meningkatkan nilai siswa dalam membaca teks narratif secara signifikan. Kata Kunci: Pre-questioning, Pemahaman Membaca, Teks Narratif.